Supporting equity, economies of scale, and interoperability by applying the International Data Space model to open science usage and impact reporting - Drummond, Christina (Septentrio Conference Series, 2022)
The OA Book Usage Data Trust effort (www.oabookusage.org) is exploring how an International Data Space (IDS) could address issues of trust, data quality, and resource-burdens for OA usage data reporting and analytics. Currently individual libraries, publishers, and scholarly publishing platforms and services must normalize, curate, and aggregate their usage and impact metrics as provided from numerous platforms. While well-resourced organizations may have the time and expertise to curate and aggregate open and privileged usage data across provided COUNTER-compliant and non-COUNTER compliant reports; smaller presses, publishers, and innovative projects often lack the resources necessary to process incoming usage data and benefit from robust OA impact analytics. To address this disparity and improve the quality and interoperability of OA book usage data, OA book publishing stakeholders are exploring how to adopt the international data space (IDS) models and standards. Awarded 1.2Million USD by the Mellon Foundation, a team led by OPERAS, OpenAIRE, the University of North Texas, and Johns Hopkins University are hosting community consultations to determine what data stewardship and security practices are needed to achieve trusted direct usage data exchange at scale.